2004
DOI: 10.1158/1078-0432.ccr-04-0891
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Feasibility and Pharmacokinetic Study of Concurrent Administration of Trastuzumab and High-Dose Chemotherapy in Advanced HER2+ Breast Cancer

Abstract: Purpose: To evaluate the safety of concurrent treatment with trastuzumab and high-dose chemotherapy (HDC), using cyclophosphamide, cisplatin, and 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU), with autologous hematopoietic progenitor cells support, in patients with HER2؉ advanced breast cancer.Experimental Design: Patients with HER2-overexpressing high-risk primary breast cancer (HRPBC; defined as >4 involved nodes or inflammatory disease), or metastatic breast cancer (MBC) were eligible. Treatment consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…Although this agent is only active in a minority (30%) of Her-2 þ tumors, treatments that enhance the activity of Herceptin should improve therapeutic outcome for a greater number of Her-2 þ patients. [5][6][7][8][9][10] In this study, we have used the novel approach of combining a gene drug (Ad-mda7) with the biological agent, Herceptin, and evaluated its antitumor effects against breast cancer cells. Preliminary results of this study have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although this agent is only active in a minority (30%) of Her-2 þ tumors, treatments that enhance the activity of Herceptin should improve therapeutic outcome for a greater number of Her-2 þ patients. [5][6][7][8][9][10] In this study, we have used the novel approach of combining a gene drug (Ad-mda7) with the biological agent, Herceptin, and evaluated its antitumor effects against breast cancer cells. Preliminary results of this study have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…7 The mda-7 gene was linked to an internal cytomegalovirus immediate early (CMV-IE) promoter and followed by Simian virus 40 polyadenylation (p(A)). Ad-Luc and AdCMVp(A) (Luciferase and empty vector, respectively) were used as control viruses.…”
Section: Recombinant Adenovirus Production and Herceptinmentioning
confidence: 99%
See 3 more Smart Citations